Long-Term Supplementation with Fruits and Vegetables Prolongs Lifespan and Reduces Tumor Incidence in Mice Fed a Western-Style High-Fat Diet. (14th June 2022) - Guo, Weimin; Wu, Dayong; Li, Lijun; Ortega, Edwin; Smith, Donald; Meydani, Simin
Abstract: Objectives: Epidemiological studies suggest that consumption of fruits and vegetables (FV) was negatively associated with the incidence of certain cancers and positively associated with life expectancy. To date, a causal relationship has not been demonstrated. The objectives of the current study were to investigate the effects of long-term FV supplementation on health- and life-span in normal weight and obese mice. Methods: Male C57BL/6J mice (5-wk) were randomly assigned to one of four groups (60/group): low fat control (LF-C, 10% kcal fat), high fat control (HF-C, 45% kcal fat), and each with 15% of a unique mixture of FV (patent pending) (w/w) (LF-FV and HF-FV). All mice were euthanized when a group reached 50% mortality. Survival analysis was performed using log-rank (Mantel-Cox) test; a two-sided Fisher's exact test was performed to compare difference in tumor incidence. Results: After 21 months of feeding, HF-C group was the first to reach 50% mortality. Further, a Kaplan-Meier survival curve demonstrated that, at termination, HF-C group had higher mortality (50.0%) compared to LF-C group (18.3%, p = 0.0008). Notably, HF-FV group had significantly lower mortality (23.3%) compared to HF-C mice (p = 0.008), and there was no significant difference in mortality between HF-FV and LF-C. Mortality was lower in LF-FV (11.7%) compared to LF-C (18.3%), although this difference was not statistically significant. Furthermore, tumor incidence in HF-C group (73.3%) was significantly higher than that in LF-C group (30.0%, p < 0.0001). HF-FV group had 23.3% lower tumor incidence compared to HF-C group (p = 0.014). There was no significant difference in tumor incidence between LF-C (30.0%) and LF-FV groups (31.7%). Conclusions: Our findings provide the first causal evidence that long-term intake of a diet supplemented with a wide variety of fruits and vegetables could extend lifespan and decrease tumor incidence in mice fed a Western-style high-fat diet. These results provide a foundation for further investigation into the benefits of fruit and vegetable supplementation on aging and age-related disease. Funding Sources: This material is based upon work supported by the U.S. Department of Agriculture – Agricultural Research Service (ARS), under Agreement No. 58–8050-9–004.